Perancangan Sistem Pendataan Santri Dan Pendataan Hafalan Berbasis Android Di Ma’had Tahfizhul Qur’an Ahlus Shuffah - Karyawati, Endang (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2024)
This research aims to further analyze how to design and implement a student data collection application at Ma'had Tahfizhul Qur'an